A Literary Review On Sutika Paricharya - Jangid, Kalpana; Gupta, Nisha; Sharma, Bhunesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
According to Ayurvedic classics, care of mother at every phase of her life, especially antenatal care (garbhini Paricharya) and postnatal care (Sutika Paricharya) is very much important. Aims and Objectives: A comparative study and review of different Acharyas and commentators related to Sutika Paricharya. Material and Method: In this review study, textual materials are used for the study from the Ayurvedic texts i.e. Charak Samhita, Sushruta Samhita, Ashtanga Hrdaya, Ashtanga Samgraha, Bhavaprakasha, Yogaratnakara and Kasayapasamhita Result: In Sutika Paricharya woman should be cared with Ahara, Vihara, Aushadi and some Pathya and Apathya to restore the health of the mother.